Los Peltephilidae (Mammalia, Xenarthra) de la Formación Collón Curá (Colloncurense, Mioceno medio), Argentina - Gonzalez Ruiz, Laureano Raúl (2013)
The Peltephilidae (Mammalia, Xenarthra) from the Collón Curá Formation (Colloncuran, Middle Miocene), Argentina. The Peltephilidae (early Eocene-late Miocene) are a group of extinct armadillos exclusive from South America, known for having horn-like osteoderms on the nasals and maxillaries. This paper discusses a nomenclatorial proposal for anatomical description of these cingulate osteoderms and describes for the fi rst time specimens of Peltephilidae (Xenarthra, Cingulata) from the Collón Curá Formation (Colloncuran, middle Miocene) of Patagonia (Argentina). The major change in the nomenclature of the osteoderms in Peltephilidae here proposed is to replace the term “central or main fi gure” by “central longitudinal elevation”. Finally, by analogy with the living species of Dasypodidae and the extinct Pampatheriidae, some considerations are presented about the relationships between the osteoderm and the overlying epidermal scale in Peltephilidae. The new specimens are assigned to Peltephilidae gen. et sp. indet., Peltephilus pumilus Ameghino and P. nanus Ameghino. The latter two species represent their youngest record and indicate a closer taxonomic affi nity of the Colloncuran age with the previous Santacrucian, instead of the subsequent Laventan and Mayoan